... ∀sp-ua ∈ Sp − Ua | sp-cr [17] = sp-r [6] ∨ sp-cr [10] = sp-r[1] → sp-r [1] := sp-cr [10], sp-r [2] := sp-cr [11], sp-r [3] := sp-cr [12], sp-r [4] := sp-cr [13], sp-r [10] := sp-cr [14], sp-r [13] := sp-cr [9], sp-r [25] := sp-cr [24], sp-r [11] := C R − R E G − DI D(sp-cr [17], sp-cr [10]), sp-r [12] := C R − R E G − SK (sp-cr [17], sp-cr [10]), sp-cr [15] := sp-r [11], sp-cr [16] := sp-r [12], sp-ua [1] := sp-r [11], sp-ua [2] := sp-r [12], Sp − Cr = Sp − Cr ∪ (sp-cr [15], sp-cr [16]) ∧ Sp − R = Sp − R ∪ (sp-r [1], sp-r [2], sp-r [3], sp-r [4], sp-r [10], sp-r [13], sp-r [11], sp-r [12], sp-r [25]) R (Reg-Sr-S) = ∀sr-cr ∈ Sr − Cr, ∀sr-r ∈ Sr − R, ∀sr-ua ∈ Sr − Ua | sr-cr [12] = sr-r [8] ∨ sr-cr [8] = sr-r[1] → sr-r [1] := sr-cr [8], sr-r [2] := sr-cr [11], sr-r [4] := sr-cr [10], sr-r [5] := sr-cr [9], sr-r [10] := sr-cr [16], sr-r [14] := sr-cr [7], sr-r [25] := sr-cr [24], sr-r [11] := C R − R E G − DI D(sr-cr [12], sp-cr [8]), sr-r [12] := C R − R E G − SK (sr-cr [12], sr-cr [8]), sr-cr [18] := sr-r [11], sr-cr [19] := sr-r [12], sr-ua [1] := sr-r [11], sr-ua [2] := sr-r [12] Sr − Cr = Sr − Cr ∪ (sr-cr [18], sr-cr [19]) ∧ Sr − R = Sr − R ∪ (sr-r [1], sr-r [2], sr-r [4],sr-r [5], sr-r [10], sr-r [14], sr-r [11], sr-r [12], sr-r [25]) ∧ Sr − Ua = Sr − Ua ∪ (sr-ua [1], sr-ua [2]) ...